2020
DOI: 10.1002/2475-8876.12193
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue‐resistant Fe‐Mn‐Si‐based alloy seismic dampers to counteract long‐period ground motion

Abstract: In recent years, resonance in high‐rise buildings due to long‐period ground motion, which induces large‐amplitude cyclic deformation of seismic dampers, has become a matter of significant concern. Performance requirements for seismic dampers that are installed in vibration‐controlled buildings have become more stringent, and durability against cyclic deformation has become essential. An Fe‐15Mn‐4Si‐10Cr‐8Ni alloy with enhanced low‐cycle fatigue resistance has been developed to produce steel seismic dampers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Related experiments have been conducted [ 23 , 28 , 75 ] and the results confirmed that the Fe-SMA seismic dampers exhibit considerably longer fatigue life (around ten times) than conventional steel dampers. Loading tests with random seismic wave inputs were also performed and the results showed that the seismic dampers exhibit stable energy absorption behavior under a wide range of deformation angles, reflecting a reliable performance during earthquake sequences [ 28 ].…”
Section: Research and Potential Engineering Applicationsmentioning
confidence: 69%
See 3 more Smart Citations
“…Related experiments have been conducted [ 23 , 28 , 75 ] and the results confirmed that the Fe-SMA seismic dampers exhibit considerably longer fatigue life (around ten times) than conventional steel dampers. Loading tests with random seismic wave inputs were also performed and the results showed that the seismic dampers exhibit stable energy absorption behavior under a wide range of deformation angles, reflecting a reliable performance during earthquake sequences [ 28 ].…”
Section: Research and Potential Engineering Applicationsmentioning
confidence: 69%
“…Recent research and development activities enable a wider use of Fe-SMA in the construction industry. In particular, the research and application of Fe-SMA over the past 10 years can be mainly divided into two fields: (1) SME-induced prestressing technique for repairing and strengthening structures [ 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ], and (2) seismic damping [ 23 , 28 , 75 ].…”
Section: Research and Potential Engineering Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, FeSMA components are mainly used for structural strengthening and retrofitting purposes [21][22][23]. Notably, full scale FeSMA BRBs have been applied in practice in Japan [24]. Meanwhile, increasing attentions were paid on exploring FeSMA as the yielding core of dampers.…”
Section: Introductionmentioning
confidence: 99%